1994
DOI: 10.1002/depr.3050020206
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in treated bipolar disorder: A one‐year prospective study using daily life chart ratings

Abstract: In this paper we describe the use of systematic retrospective and prospective life chart methodology and document the substantial morbidity experienced even in closely monitored and aggressively treated bipolar patients rated on a daily basis for 1 year. 35 BP I (n = 26) and BP II (n = 9) patients were recruited for an ongoing treatment study comparing the prophylactic effects of lithium or carbamazepine for 1 year with a crossover to the other drug in the second year, and a third year on the combination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Two recent maintenance studies have reported that lithium was not superior to placebo in delaying a new depressive episode, whereas lamotrigine was superior to placebo, with similar results in a combined analysis (Bowden et al, 2003a;Calabrese et al, 2003;Goodwin et al, 2004). An earlier maintenance study of lithium indicated an increased rate of depressive episodes in both rapid cycling and nonrapid cycling patients compared with placebo (Dunner et al, 1976), and a crossover study indicated little long-term benefit on depressive symptoms in bipolar disorder (Denicoff et al, 1994). However, a plausible mechanism for the worsening of depression, we observed in the initially euphoric manic patients treated with lithium is not selfevident.…”
Section: Discussionmentioning
confidence: 46%
“…Two recent maintenance studies have reported that lithium was not superior to placebo in delaying a new depressive episode, whereas lamotrigine was superior to placebo, with similar results in a combined analysis (Bowden et al, 2003a;Calabrese et al, 2003;Goodwin et al, 2004). An earlier maintenance study of lithium indicated an increased rate of depressive episodes in both rapid cycling and nonrapid cycling patients compared with placebo (Dunner et al, 1976), and a crossover study indicated little long-term benefit on depressive symptoms in bipolar disorder (Denicoff et al, 1994). However, a plausible mechanism for the worsening of depression, we observed in the initially euphoric manic patients treated with lithium is not selfevident.…”
Section: Discussionmentioning
confidence: 46%
“…In one acute mania study (Post et al 1987) and several prophylaxis studies (Okuma et al 1973;Post et al 1983;Elphick 1985), a high percentage of response was observed in rapid-cycling patients. However, when rapidcycling patients were compared with non-rapid-cycling patients in the recent studies of Okuma (1993), andDenicoff et al (1994, andunpublished observations) in our group, both found a higher prophylactic response rate to carbamazepine in non-rapid cycling patients. Okuma's data are revealing in that the 53% response rate to carbamazepine in those patients with a history of rapid cycling (compared with 76% in those without) is still substantially higher than the 30% response rate observed for lithium in patients with a history of rapid cycling (compared with 64% in those without such a history).…”
Section: Potential Correlates Of Response To the Mood Stabilizersmentioning
confidence: 64%
“…Lithium response rates of 80% continue to be cited in many articles and text books, yet the largest controlled trial of lithium in acute mania showed only 50% improvement after three weeks in approximately 50% of the patients, in an intentto-treat analysis (Bowden et al 1994). Similarly, a substantial series of studies in many academic and clinical settings also reveals that some 50% of patients may show inadequate prophylactic response (Prien et al 1988;Gelenberg et al 1989;Maj et al 1989;Aagaard and Vestergaard 1990;Harrow et al 1990;O'Connell et al 1991;Vestergaard 1992;Denicoff et al 1994;Gitlin et al 1995). Moreover, under the rubric of "lithium therapy", lithium carbonate is often not the only drug used as it is frequently augmented by antidepressants and neuroleptics or benzodiazepines.…”
Section: Introductionmentioning
confidence: 89%
“…50 % of patients (Bowden et al, 1994). Furthermore, many studies have suggested that a similar proportion of patients may have an inadequate prophylactic response to lithium, the most recent being Denicoff et al (1994) and Gitlin et al (1995). In addition, the side-effect profile of lithium makes compliance a significant problem.…”
Section: Current Therapymentioning
confidence: 97%